MUDRA –A boost for upraising microenterprises and employment in Jammu and Kashmir UT since its inception. (International Journal of Food and Nutritional Sciences, 2023)
For the development and refinancing micro unit’s enterprises Govt of India setupa financial institution called Mudra-which stands for micro units development and refinanceagency Ltd.